FAKTA TEOLOGIS-SAINTIFIK TENTANG GUNUNG: PERSPEKTIF AL-TAFSÎR AL-‘ILMÎ - Maya, Rahendra; Sarbini, Muhammad; Herman, Herman; Hidayati, Hidayat; Alfarisi, Muhammad Fadilah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The mountains with the terms jabal and jibâl as well as with the term rawâsî and its derivatives are mentioned in the Qur'an 33 times in 30 letters that reveal theological-scientific facts about it in its various aspects. This phenomenon has attracted the attention and interest of researchers based on the scientific miracle aspect in the Qur’an (al-I’jâz al-‘ilmî fî Al-Qur’ân) which then became a popular discipline as scientific-scientific interpretation (al-tafsîr al-‘ilmî). This study uses a descriptive qualitative method with a literature study approach with data collection techniques through literature-documentary studies with data analysis techniques using content analysis based on the perspective of al-tafsîr al-maudhû’î al-‘ilmî. The results of the study show theological-scientific facts about mountains studied based on al-tafsîr al-‘ilmî from various related works, including mountains that tower high, as earth pegs, always moving like clouds, their various colors according to their metal content, and as a place to live and mountains always glorify and worship only Allah.